THE INFLUENCE OF ACCESS TO CREDIT ON SMALL SCALE COFFEE PRODUCTION IN KANGUNDO SUB-COUNTY, MACHAKOS COUNTY, KENYA - Kaula, Francis Mutethya; Arasa, Robert; Nzioki, Susan (International Journal of Economics, Commerce and Management, 2019)
Despite many government interventions aimed at reviving the declining coffee industry in Kenya, the quality and quantity of Kenyan coffee is deteriorating. Research has shown that farmers are not applying production inputs due to lack of capital. The study reported in this paper adopted a descriptive survey design and was carried out with an aim of determining how access to credit influences small scale coffee production in Kangundo Sub-county. The study randomly sampled 2 factories in each of the 6 societies and included 370 farmers who were randomly selected. A validated and vetted questionnaire was administered to selected farmers. The results show that: less than half (42.0%) of farmers do not have collateral to secure loans; almost a third (31.1%) of farmers cannot get a guarantor to secure a loan; majority (69.2%) of the farmers cited interests charged on loans are quite high; and majority (43.3%) of farmers indicated that they do not have a solid financial relationship with lenders. The paper recommends that the national and county government should consider coming up with a preferential coffee credit facility with features such as: a grace period of 12 months; preferential low interest rates; and with government guaranteeing each loan taken. The study recommends that future studies should explore on other variables such as climate change, land succession, age and gender.
Keywords: Small Scale Farmers, Access To Credit, Collateral Requirement, Interest Rates, Financial Relationship